Cytogenetic variability and new chromosome number reports in Silene L. species (Sect. Lasiostemones, Caryophyllaceae) - Sheidai, Masoud; Nikoo, Mehrnoosh; Gholipour, Abbas (Acta Biologica Szegediensis, 2008)
Karyotype and meiotic studies were performed in 19 populations of five Silene species of the section Lasiostemones Boiss., growing in Iran. The species of S. longipetala, S. tenella, S. claviformis and S. Marschallii possessed 2n = 2x = 24 chromosome number, while S. propinqua populations were diploid and tetraploid with two different base number of x = 10 and 12 (2n = 4x = 40). The results obtained support the earlier report on S. Marschallii while the chromosome number of S. longipetala, S. tenella, S. claviformis and S. propinqua are new to science. The chromosomes were mainly metacentric and sub-metacentric. The species studied differed significantly in total size of the chromosomes, size of the short arms and the long arms, indicating the role of quantitative genomic changes in the Silene species diversification. They also differ in their karyotypic formulae indicating the occurrence of structural changes in their chromosomes. The Silene species were placed in 1A, 2A and 1B classes of Stebbins karyotype symmetry which are considered relatively primitive in this system. PCA ordination of the Silene species indicated karyotypic distinctness of the species studied. Meiotic analysis showed that Arak population of S. Marschalii forms quadrivalents due to the occurrence of heterozygote translocation between two pairs of chromosomes which in turn may increase the amount of genetic variability in the next generation. Unreduced pollen grains were formed in populations of S. Marschalii due to multipolar cell formation, while B-chromosomes were observed in some of the species studied.